2008
DOI: 10.1007/s00436-008-1172-4
|View full text |Cite
|
Sign up to set email alerts
|

Neem seed extract shampoo, Wash Away Louse®, an effective plant agent against Sarcoptes scabiei mites infesting dogs in Egypt

Abstract: In the present study, the efficacy of water-free neem seed extract shampoo Wash Away Louse, provided by Alpha-Biocare GmbH, Düsseldorf (Germany), was investigated against Sarcoptes scabiei infesting dogs in Egypt. Ten naturally infested dogs were collected from different areas in the Nile delta. The occurrence of lesions, hair loss, and skin inflammation were regarded as signs of infestation and proved by detection of adult parasites and their developmental stages in scrapings of infested lesions. Adequate amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
1
Order By: Relevance
“…They have been used for a long time by practitioners of traditional medicine on account of their pharmacological activity and low toxicity. In the recent past various studies have been carried out to develop environmentally safe control measures against ectoparasites and attempts have been made to identify insecticidal/acaricidal properties of different botanical compounds against lice [ 20 , 21 ], mosquitoes [ 22 ], flies [ 23 ], ticks [ 7 , 8 ], and mites [ 24 ]. However, in order to offer a complete ecofriendly acaricide, there is a need to assess botanical extracts, especially from plants which are rustic, perennial, and easily cultivable and have a better potential of extension, in addition to their inherent acaricidal properties.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used for a long time by practitioners of traditional medicine on account of their pharmacological activity and low toxicity. In the recent past various studies have been carried out to develop environmentally safe control measures against ectoparasites and attempts have been made to identify insecticidal/acaricidal properties of different botanical compounds against lice [ 20 , 21 ], mosquitoes [ 22 ], flies [ 23 ], ticks [ 7 , 8 ], and mites [ 24 ]. However, in order to offer a complete ecofriendly acaricide, there is a need to assess botanical extracts, especially from plants which are rustic, perennial, and easily cultivable and have a better potential of extension, in addition to their inherent acaricidal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Other workers (Omar et al 2003) have demonstrated that purified extracts of Azadirachta indica and other members of the Meliaceae family containing gedunin showed significant in vitro, but poor in vivo, antimalarial activity. Patented di-basic-ester extracts of A. indica have been proven in several in vivo and in vitro tests to eliminate infestations with head lice, P. humanus capitis (Heukelbach et al 2006;Abdel-Ghaffar and Semmler 2007); scabies mites, Sarcoptes scabiei (Abdel-Ghaffar et al 2008b); or red chicken mites, Dermanyssus gallinae (Abdel-Ghaffar et al 2008a. Seed extracts of A. indica, Vitex agnus castus and Eucalyptus citriodora oil were tested on repellent effects against mosquitoes, Aedes aegypti, Culex quinquefasciatus, ticks, Ixodes ricinus, Dermacentor reticulates, Rhipicephalus sanguineus, head lice, P. humanus capitis, and mites, Dermanyssus gallinae ).…”
Section: Introductionmentioning
confidence: 99%
“…Um grupo permaneceu sem tratamento, grupo controle, e o outro foi medicado. A dosagem, frequência e duração do tratamento foram estipuladas de acordo com trabalhos que utilizaram o extrato de nim, no controle de outros parasitos e em diferentes espécies, uma vez que até o presente momento não há relatos na literatura sobre a utilização do medicamento em coelhos infestados por P. ovis (Abdel-Ghaffar et al 2008, Fernandes et al 2010, Schmahl et al 2010.…”
Section: Methodsunclassified